ANALYSIS ON STUDENTS’ ENGLISH SPEAKING PERFORMANCE AT UNIVERSITY OF MUHAMMADIYAH SUMATERA UTARA - Yayuk Hayulina Manurung (UIN Sumatera Utara, 2020)
The lack of students’ English-speaking performance seems tobe common problems found in the department of Englisheducation at the University of Muhammadiyah SumateraUtara. Those problems involve the lack of fluency andproficiency in English speaking skills. This study aimed toanalyze the students’ English-speaking performance and thechallenges faced by them. This research applied a descriptivequalitative design. The data such as the documents,observation, and interviews were applied. In analyzing thedata concerning the components of data analysis in theinteractive model, it was proposed by Miles and Huberman(2016). The data were taken questionnaire from 125 EFL ofsecond-year students were collected, then the researcher alsoconducted the individual interviews with lecturers and classobservation. The result showed that the most challengingfactor faced by the students' speaking performance was relatedto the students themselves. Speaking errors were frequentlymade. The errors dominantly covered into 3 categories namelymisused forms (44.8 %), incorrect omission (33.6%), andmisplaced and confusing words (21.2 %). Concerning theexternal factors, the updated teaching strategies should beapplied in terms of reducing the use of the mother tongue bycombining various speaking performances, collaborating withother lecturers to organize more English programs, and sharethe speaking teaching experience.